Serum neuron-specific enolase, magnetic resonance imaging, and electrophysiology for predicting neurodevelopmental outcomes of neonates with hypoxic-ischemic encephalopathy: a prospective study - Hui-Zhi Huang; Xiao-Feng Hu; Xiao-Hong Wen; Li-Qi Yang (BMC Pediatrics, 2022)
Abstract Background Neonatal hypoxic-ischemic encephalopathy (HIE) is an important cause of mortality and morbidity. Effective indicators for the early diagnosis of brain injury after HIE and prognosis are lacking. This study aimed to examine the predictive value of serum neuron-specific enolase (NSE), amplitude-integrated electroencephalography (aEEG), and magnetic resonance imaging (MRI), alone and in combination, for the neurological outcomes in neonates with HIE. Methods Newborns with HIE born and treated at the Third Affiliated Hospital of An-Hui Medical University were consecutively included in this prospective cohort study (June 2013 to December 2020). Encephalopathy was classified as mild, moderate or severe according to Samat and Sarnat. All patients were assessed serum 1-day NSE and 3-day NSE levels after birth. The children were classified by neurological examination and Bayley Scales of Infant Development II at 18 months of age. ROC analysis was used to evaluate the predictive accuracy of the neurodevelopment outcomes. Results A total of 50 HIE neonates were enrolled (normal group: 32 (64.0%), moderate delay: 5 (10.0%), severe delay: 30(26.0%)) according to Bayley II scores. Serum 3-day NSE levels increased with worsening neurodevelopment outcomes (normal: 20.52 ± 6.42 μg/L vs. moderate: 39.82 ± 5.92 μg/L vs. severe: 44.60 ± 9.01 μg/L, P < 0.001). The MRI findings at 4–7 days after birth were significantly different among the three groups (P < 0.001). Forty-two (84.0%) children had abnormal aEEG. The combination of the three abnormalities combined together had 100% sensitivity, 97.70% specificity, 98.25% PPV, and 99.98% NPV. Conclusions MRI, aEEG, and 3-day NSE can predict the neurological prognosis of newborns with HIE without hypothermia treatment. Their combination can improve the predictive ability for long-term neurobehavioral prognosis.